A gender perspective on the human capital returns of hospitality firm's managers - Sánchez-Ollero, José Luis; García-Pozo, Alejandro (My University, 2018)
The aim of this paper is to analyze the evolution of existing differences in human capital returns and in other variables considered in this analysis among the business managers of the hospitality sector, paying special attention to identifying which of these differences are due to being a woman and which are due to differences in productivity between workers of both genders. The methodology applied is based on the theory of human capital (Becker, 1964). Subsequently, the well-known methodology of Oaxaca-Blinder (1973) is applied to estimate differences due to gender discrimination and those due to differences in productivity. The results of the descriptive statistics show that between 2010 and 2014 the gross hourly wages of male managers continue to be higher than those of women managers, but there is a significant decrease in the gap between both groups, with women´s wages as a proportion of men´s wages rising from 67.45% in 2010 to 76.38% in 2014. Moreover, the estimations made using the Mincerian equation indicate that while the returns on education for male managers remain stable in this period, those of women go from not being statistically significant to 4.1% per additional year of education. Finally, the wage discrimination based on gender between managers of the hospitality sector has been significantly reduced in this period of economic crisis since in 2010 it was 66% and in 2014 it only reaches 58%.
Keywords: Recursos humanos; Human capital; Wages; Productivity; Gender wage gap; Gender discrimination; Hospitality